Whole-Genome Sequence of a Beak and Feather Disease Virus Isolate from a Fledgling Red-Capped Parrot (Purpureicephalus spurius) - Das, Shubhagata (Genome Announc, 2016)
The complete genome sequence of beak and feather disease virus (BFDV) from a fledgling red-capped parrot (Purpureicephalus spurius) was assembled and characterized. The genome consists of 1,995 nucleotides and encodes two major proteins in opposing directions. This is the first evidence of BFDV infectivity and a complete genome sequence for this novel host.